Efektivitas Inquiry Learning di Sekolah Menengah Kejuruan melalui Meta-Analisis Dampak Manfaat dan Tantangan - Sofi, Abdullah; Wagino, Wagino; Purwanto, Wawan; Sugiarto, Toto; Koto, Rahmat Desman; Abizar, Haris; Sa'adah, Agis Amelia (PAKAR Pendidikan, 2025)
Inquiry-based learning is an approach that emphasizes students’ active involvement in the learning process through inquiry and exploration. In Vocational High Schools (SMK), there is an urgent need to improve students’ critical thinking, problem-solving, and technical skills to harmonize with the demands of the world of work. However, the effectiveness of the implementation of inquiry learning in vocational schools is still diverse and requires a comprehensive study. This study aims to evaluate the effectiveness of inquiry learning in vocational schools through a meta-analysis approach to the results of previous research. Literature searches were conducted through Google Scholar with the keywords “inquiry learning,” “inquiry learning,” “vocational schools,” and “learning outcomes” in the 2019-2024 publications. Inclusion criteria include experimental research with control groups, vocational school student subjects, and complete post-test data. The selection process resulted in 30 studies that met the criteria. The extracted data included the mean and standard deviation post-test of both groups. The analysis uses Cohen’s effect size formula to calculate the impact of inquiry learning. The results showed an effect size of 1.0, which indicated a significant influence of inquiry learning on the learning achievement of vocational school students, especially in understanding concepts and practical skills. However, implementation challenges include limited time, resources, and teacher readiness. It is concluded that inquiry learning is efficacious in improving the learning outcomes of vocational students but requires an implementation strategy that considers contextual factors.